Character Education and Love of the Homeland: Integration of National Values in the Primary School Curriculum - Monigir, Norma; Tarusu, Deysti (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to analyze the implementation of character education in fostering a sense of love for the homeland in grade V students at 7 Tondano State Elementary School, Minahasa Regency, North Sulawesi. Character education is an important foundation in shaping a young generation that is not only intellectually intelligent but also has integrity, social responsibility, and strong nationalism. Methodology: Data was collected using a qualitative descriptive approach through observation, interviews, and documentation studies of learning activities, extracurricular activities, and teaching tools related to national values. Main Findings: The study's findings show that the values of love for the homeland are consistently integrated in the learning of Pancasila and Citizenship Education, and strengthened through school activities such as flag ceremonies, community service, and national holiday celebrations. The active role of teachers and principals as role models and creators of school culture that supports national character is the main factor in the implementation’s success. Despite this, challenges are still encountered, especially regarding the limitations of engaging learning media and limited time in the curriculum. This study contributes to developing character education practices in primary schools by emphasizing the importance of a contextual approach based on local culture. Novelty/Originality of this Study: This study's uniqueness lies in its incorporation of traditional Minahasa values such as cooperation (mapalus) into the formation of the character of love for the homeland, as well as recommendations for strengthening through innovative learning media relevant to the digital era.